Investment Factors in Bitcoin based on UTAUT: Indonesian Investor - Tamara, Dewi; Maharani, Anita (Faculty of Economics, Universitas Sriwijaya, 2024)
Bitcoin gained significant popularity starting in 2017, when the price soared from around 1,000 at the beginning year to nearly 20,000 in December. The aim of this research to analyze the factors of investment in bitcoin in Indonesia. The population of the study is individual who invest in Bitcoin. The sample is purposive with 140 valid respondentsfrom social media bitcoin group. The research used quantitative with online survey, distributed during September to November 2022.The survey was analysed using Structural Equation Modelling with Smart PLS. This study found that the facilitating conditions, compatibility, trust, power prestige, and retention time positively influence the investing intention in Bitcoin. Moreover, Awareness does not have significant effect on investment intention. Gender does not moderate the facilitating conditions, awareness, compatibility, trust, power prestige, and retention time with intention to invest in Bitcoin. It implies that the provider should pay attention more on facilitating conditions, compatibility, and retention time of the Bitcoin investment in their platform.